2010
DOI: 10.1200/jco.2010.29.7978
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation Therapy With Subcutaneous Alemtuzumab After Fludarabine and Rituximab Induction Therapy for Previously Untreated Chronic Lymphocytic Leukemia: Final Analysis of CALGB 10101

Abstract: A B S T R A C T PurposeTo determine if alemtuzumab consolidation improves response rate and progression-free survival (PFS) after induction chemoimmunotherapy in previously untreated symptomatic patients with chronic lymphocytic leukemia. Patients and MethodsPatients (n ϭ 102) received fludarabine 25 mg/m 2 intravenously days 1 to 5 and rituximab 50 mg/m 2 day 1, 325 mg/m 2 day 3, and 375 mg/m 2 day 5 of cycle 1 and then 375 mg/m 2 day 1 of cycles 2 to 6; fludarabine plus rituximab (FR) administration was repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 27 publications
1
48
0
3
Order By: Relevance
“…While several of these studies have shown that alemtuzumab consolidation is efficacious in achieving an MRD-negative state and results in better clinical responses and response duration, it is important to recognize that this treatment can be associated with myelosuppression, opportunistic infections, and other complications, and that these may offset its clinical benefit. 30 Alemtuzumab should be administered within clinical trials and not before at least 6 months have passed from the last chemotherapy regimen.…”
Section: Consolidation Therapy: Eradication Of Mrdmentioning
confidence: 99%
“…While several of these studies have shown that alemtuzumab consolidation is efficacious in achieving an MRD-negative state and results in better clinical responses and response duration, it is important to recognize that this treatment can be associated with myelosuppression, opportunistic infections, and other complications, and that these may offset its clinical benefit. 30 Alemtuzumab should be administered within clinical trials and not before at least 6 months have passed from the last chemotherapy regimen.…”
Section: Consolidation Therapy: Eradication Of Mrdmentioning
confidence: 99%
“…In fact, very few studies have demonstrated a clear benefit from MRD eradication or consolidation therapy in CLL, 31,32 and some of the strategies tested, although effective, resulted in significant toxicity. [33][34][35] Thirdly, it could be argued that MRD assessment is simply a surrogate for evalution of other adverse prognostic markers since, for instance, patients with a 17p A proportion of patients with chronic lymphocytic leukemia achieve a minimal residual disease negative status after therapy. We retrospectively evaluated the impact of minimal residual disease on the outcome of 255 consecutive patients receiving any front-line therapy in the context of a detailed prognostic evaluation, including assessment of IGHV, TP53, NOTCH1 and SF3B1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In CLL, maintenance or consolidation therapies with different drugs, including interferon-a, 10,11 rituximab, [12][13][14][15][16][17][18] alemtuzumab, [19][20][21][22][23][24][25][26][27] or more recently lenalidomide, 28 have been evaluated. As with other B-cell malignancies, the use of rituximab maintenance after induction treatment suggests a benefit in sustaining the response duration in patients with CLL.…”
Section: Introductionmentioning
confidence: 99%